An Insight into Spin Supercurrent: Physical Aspect of Some Magic Rites - Liudmila B. Boldyreva (Fundamental Research and Application of Physical Science Vol. 9, 2023)
The study is split into two categories under the research’s objective: theoretical and experimental. Some of the alleged miracles performed by modern and ancient magicians-often referred to as "psychics"-are as follows: 1) the selective action on distant objects (especially "contagious magic"); 2) the discovery of hidden cavity structures (underground water reservoirs, buried treasures, etc.); 3) the structuring of space around a psychic (the so-called magic rings or charmed rings, allegedly protecting against malicious influence); 4) the alteration of a person’s own weight (particularly levitation); and 5) the capacity to become invisible. These miracles might emerge from phenomena occurring in the physical vacuum, which characterized by intrinsic angular momentum: A quantum entity produces a pair of oppositely charged virtual particles with spin (virtual photon) in this vacuum. Because the virtual photon has precessing spin, it can be categorized as a spin vortex. Spin vortices in this vacuum can interact through spin supercurrent, the value of which is determined by the mutual orientation of spins of interacting spin vortices. From a physical perspective, a person’s capacity to perform a miracle depends on their capacity to control the properties of spins (orientation, precession frequency, etc.) of spin vortices produced in the vortex-type physical vacuum by quantum entities that make up their organism.